FACTORS AFFECTING TEN GRADERS’ ATTITUDES ON LEARNING ENGLISH AS A FOREIGN LANGUAGE AT SMAN 8 KOTA BENGKULU - Nababan, Riama; Lubis, Azhar Aziz; Arasuli (Wacana: Jurnal Penelitian Bahasa, Sastra dan Pengajaran, 2025)
This survey research aims to determine the factors affecting students' attitudes toward learning English positively and negatively at SMA N 8 Kota Bengkulu. The population in this study were all grade 10 students, including science and social studies classes, with a total of 316 students with a sample 177 students using a random sampling technique. This study uses a questionnaire to collect data adapted from Getie's research (2020). Then the data was analyzed using the SPSS 25 application. The results showed that students had a positive attitude toward learning English (78%). However, it was found that the anxiety speaking in class factor has affected students' attitudes negatively (74,3%). The educational context factor has affected them positively (78,5%); however, the findings show that learning materials have affected their attitudes negatively (59,1%). The social context factor has affected their attitude positively (72,6%). The age factor has influenced their attitude positively (76,3%). However, the gender factor students do not believe that gender can affect their attitude toward learning English (66,7%). These results suggest that teachers should continue to approach students to resolve their anxiety.